2010
DOI: 10.1021/la100449z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BET Method for Determining Surface Areas of MOFs and Zeolites that Contain Ultra-Micropores

Abstract: The BET analysis is commonly used for determining surface areas of metal-organic frameworks (MOFs) and zeolites that contain "ultra-micropores" (<7 A) even though it is often stated that the BET surface areas obtained for such small pores are not really meaningful in an absolute sense. In this study, nitrogen and argon isotherms in MOFs and zeolites (most of them having ultra-micropores) were predicted by grand canonical Monte Carlo (GCMC) simulations and used as pseudoexperimental data to evaluate the BET met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
207
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(223 citation statements)
references
References 24 publications
13
207
1
2
Order By: Relevance
“…Their theoretical BET surface areas deduced from experimental isotherms (360 and 429 m 2 g À1 , respectively) are much more reliable than the accessible surface areas (0 and 149 m 2 g À1 ) and fit well the experimental value. This result can be related to previous studies [29] which have emphasized that the side pockets of the mordenite type zeolite cannot be probed using the geometric method. Thus, the geometric approach is not suitable for adsorbents with a pore size comparable to those of N 2 .…”
supporting
confidence: 86%
“…Their theoretical BET surface areas deduced from experimental isotherms (360 and 429 m 2 g À1 , respectively) are much more reliable than the accessible surface areas (0 and 149 m 2 g À1 ) and fit well the experimental value. This result can be related to previous studies [29] which have emphasized that the side pockets of the mordenite type zeolite cannot be probed using the geometric method. Thus, the geometric approach is not suitable for adsorbents with a pore size comparable to those of N 2 .…”
supporting
confidence: 86%
“…The N 2 adsorption and desorption isotherms of the obtained materials were measured (BEL Japan, Inc., Belsorp mini), and the total surface area, external surface area and micropore volume were calculated using the BET and t-methods [28].…”
Section: Characterization Of Zeolitementioning
confidence: 99%
“…It has been often reported that Ar should be used over N 2 for the analysis of microporous materials particularly zeolites because of the validity of the monolayer capacity. However, Bae et al [19] used both gases to determine the surface areas for ultramicroporous materials and found results to be in good agreement.…”
Section: Bet and Sem Analysismentioning
confidence: 99%